2022
DOI: 10.2147/dddt.s363766
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Super-Activated Platelet Lysate on Early Healing of Tooth Extraction Sockets in Rats

Abstract: Purpose To evaluate the effect of super-activated platelet lysate (sPL) on wound healing of tooth extraction sockets in rats. Methods Rat models of the tooth extraction socket were established. Thirty-six rats were divided into control and sPL groups and sacrificed on days 7, 14, and 28 after tooth extraction. Bone formation in tooth extraction sockets were observed by microscopic computed tomography (micro-CT) and hematoxylin and eosin (HE) staining; osteoprotegerin (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
(66 reference statements)
0
2
0
Order By: Relevance
“…Hence, thirty-six albino Wistar rats (35 days old) [23] of either sex, weighing 180-200 g [24], were procured from the University of Veterinary and Animal Sciences, Lahore, Pakistan for this study. Animals that were pregnant or died during the study period were excluded [25].…”
Section: Methodsmentioning
confidence: 99%
“…Hence, thirty-six albino Wistar rats (35 days old) [23] of either sex, weighing 180-200 g [24], were procured from the University of Veterinary and Animal Sciences, Lahore, Pakistan for this study. Animals that were pregnant or died during the study period were excluded [25].…”
Section: Methodsmentioning
confidence: 99%
“…The article [7]: 36 rats were divided into two groups: the first group of mice ( 18) -after tooth extraction, they were injected with super active platelet lysate; the second group (18) -control group, after extraction, 2 ml of saline was injected. According to the MRI results, it was concluded that in the first group, bone tissue deposition was noticed 10 days after tooth extraction, but in the control group there was no such bone volume as in the first group.…”
Section: The Use Of Super Active Platelet Lysate As a Stimulating Sub...mentioning
confidence: 99%